The Descendants of Japanese Immigrants in Brazil and “Eye Westernization Surgery” (Antropolítica - Revista Contemporânea de Antropologia, 2022)
This article examines some of the contemporary forms of invention and construction of Japanese-Brazilian identity. For these purposes, I concentrate on the body practices referred to as “westernization” in which Japanese-Brazilians have engaged – in particular, “eye westernization” surgery. In the case of the nikkei, the shape of the eyes is the physical trait that most sharply elicits “appearance- based racism.” Racism and discrimination, which focus on phenotype, exist in direct relation to the more than hundred year presence of the Japanese and their descendants at the heart of Brazilian society, that is, in a country that is home to the largest Japanese community outside of Japan. These “westernization” body practices, as well as the beauty standards they give expression to, act and react upon Brazilian society, shaping the group’s ethnic and social profile.